Phase 1 randomized controlled trial to evaluate the safety and immunogenicity of recombinant Pichia pastoris-expressed Plasmodium falciparum apical membrane antigen 1 (PfAMA1-FVO [25-545]) in healthy Malian adults in Bandiagara. (December 2016) - Thera, Mahamadou; Coulibaly, Drissa; Kone, Abdoulaye; Guindo, Ando; Traore, Karim; Sall, Abdourhamane; Diarra, Issa; Daou, Modibo; Traore, Idrissa; Tolo, Youssouf; Sissoko, Mady; Niangaly, Amadou; et al.
Abstract Background The safety and immunogenicity of PfAMA1, adjuvanted with Alhydrogel® was assessed in malaria–experienced Malian adults. The malaria vaccine, PfAMA1-FVO [25-545] is a recombinant proteinPichia pastoris -expressed AMA-1 fromPlasmodium falciparum FVO clone adsorbed to Alhydrogel®, the control vaccine was tetanus toxoid produced from formaldehyde detoxified and purified tetanus toxin. Methods A double blind randomized controlled phase 1 study enrolled and followed 40 healthy adults aged 18–55 years in Bandiagara, Mali, West Africa, a rural setting with intense seasonal transmission ofP. falciparum malaria. Volunteers were randomized to receive either 50 µg of malaria vaccine or the control vaccine. Three doses of vaccine were given on Days 0, 28 and 56, and participants were followed for 1 year. Solicited symptoms were assessed for seven days and unsolicited symptoms for 28 days after each vaccination. Serious adverse events were assessed throughout the study. The titres of anti-AMA-1 antibodies were measured by ELISA andP. falciparum growth inhibition assays were performed. Results Commonest local solicited adverse events were the injection site pain and swelling more frequent in the PfAMA1 group. No vaccine related serious adverse events were reported. A significant 3.5-fold increase of anti-AMA-1 IgG antibodies was observed in malaria vaccine recipients four weeks after the third immunization compared to the control group. Conclusion The PfAMA1 showed a good safety profile. Most adverse events reported were of mild to moderate intensity. In addition, the vaccine induced a significant though short-lived increase in the anti-AMA1 IgG titres. Registered onwww.clinicaltrials.gov with the number NCT00431808